Immunotherapy for Lung Cancer: No Longer an Abstract Concept - Marrone, Kristen A.; Naidoo, Jarushka; Brahmer, Julie R. (Seminars in Respiratory and Critical Care Medicine, 2016)
The treatment paradigm for lung cancer has been transformed in recent years by the use of immunotherapy, specifically, immune checkpoint antibodies (mAb), which are agents designed to reinvigorate an immune-mediated anticancer response by releasing the effects of tumor-mediated immunosuppression. Late-phase clinical trials of these agents in patients with advanced lung cancers have translated into improved clinical outcomes compared with standard-of-care chemotherapy for the treatment of metastatic non-small cell lung cancer, and have resulted in FDA approvals for two immune checkpoint mAbs in the second-line setting. In addition, promising results have been seen in early-phase clinical studies in small cell lung cancer (SCLC) and for immune checkpoint combinations in NSCLC thus far. While the efficacy of these agents is exciting, they have also been associated with a unique profile of immune-mediated toxicity that is distinct from classic cytotoxic therapies. As these agents move into the lung cancer clinic, we must seek to maximize the therapeutic potential of this class of agents through optimization of patient selection, improved response assessments, and exploring rational combinations of immune checkpoint mAbs with other potentially synergistic therapies, to improve response rates and extend the “tail on the curve.”
Keywords: immunotherapy; immune checkpoint antibody; anti-CTLA-4; anti-PD-1; anti-PD-L1; non-small cell lung cancer; small cell lung cancer; lung cancer